Antimicrobial and Antibiofilm Activity of Chitosan on the Oral Pathogen Candida albicans - Costa, Eduardo (Pathogens, 2014)
Oral candidiasis is particularly evident, not only in cancer patients receiving chemotherapy, but also in elderly people with xerostomy. In general, Candida is an opportunistic pathogen, causing infections in immunocompromised people and, in some cases, when the natural microbiota is altered. Chitosan, a natural derivative of chitin, is a polysaccharide that has been proven to possess a broad spectrum of antimicrobial activity that encompasses action against fungi, yeast and bacteria. While recent studies have revealed a significant antibiofilm activity upon several microorganisms, including C. albicans, little is known regarding the impact of chitosan upon the adhesive process or mature biofilms. With that in mind, the purpose of this work was to evaluate, in vitro, the capability of chitosan to inhibit C. albicans growth and biofilm formation. The results obtained showed that chitosan is capable of inhibiting C. albicans planktonic growth (HMW, 1 mg/mL; LMW, 3 mg/mL). Regarding biofilm growth, chitosan inhibited C. albicans adhesion (ca. 95%), biofilm formation (percentages above 90%) and reduced mature biofilms by ca. 65% and dual species biofilms (C. albicans and S. mutans) by ca. 70%. These results display the potential of this molecule to be used as an effective anti-Candida agent capable of acting upon C. albicans infections.